2021
DOI: 10.3390/membranes11090653
|View full text |Cite
|
Sign up to set email alerts
|

Rejection Capacity of Nanofiltration Membranes for Nickel, Copper, Silver and Palladium at Various Oxidation States

Abstract: Electroplating and metalworking industries produce enormous amounts of waste containing heavy metals in their effluents, leading to potential threats to biotic and abiotic life. According to regulation, heavy metal contamination must be kept within the regulated standard of a few parts per million, which has led to a recent pique in interest in the utilization of nanofiltration technology for metal recovery. The effect of feed pH, pressure, metal concentration, and oxidation of metal on the rejection of heavy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Consequently, a better approach would be to select nanoparticles that specifically interact with heavy metal ions. The thiol (SH) functional groups enhance heavy metal adsorption through complexation [38]. They can be introduced into TFN membranes via, for example, L-cysteine functionalized cellulose nanocrystals [35].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, a better approach would be to select nanoparticles that specifically interact with heavy metal ions. The thiol (SH) functional groups enhance heavy metal adsorption through complexation [38]. They can be introduced into TFN membranes via, for example, L-cysteine functionalized cellulose nanocrystals [35].…”
Section: Discussionmentioning
confidence: 99%
“…This behavior could be explained the smallest pore size of SR90 and BW30 membranes, or to the higher electrostatic interaction between the NF90 and NFS membranes and the Mg 2+ , resulting in a reduction of the salt rejection for these membranes. Thabo et al (2021) [42] also observed higher rejections of Na + in NF270 and NF90 membranes and lower rejections of Mg 2+ , attributing this result to the charge effects of these membranes governed by Donnan exclusion.…”
Section: (A) (B) (C) (D)mentioning
confidence: 90%
“…Brooms Thabo et al [12] compared three commercially available nanofiltration membranes. They chose two polyamide membranes: NF90 (MWCO = 150 Da), NF270 (MWCO = 200 Da), and one polypiperazine, PP-NF (MWCO = 150 Da).…”
Section: Nanofiltrationmentioning
confidence: 99%